2017
DOI: 10.1038/s41598-017-05657-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the Oxidative Folding Pathway of the High Affinity Nerita Versicolor Carboxypeptidase Inhibitor (NvCI)

Abstract: Nerita Versicolor carboxypeptidase inhibitor (NvCI) is the strongest inhibitor reported so far for the M14A subfamily of carboxypeptidases. It comprises 53 residues and a protein fold composed of a two-stranded antiparallel β sheet connected by three loops and stabilized by three disulfide bridges. Here we report the oxidative folding and reductive unfolding pathways of NvCI. Much debate has gone on whether protein conformational folding guides disulfide bond formation or instead they are disulfide bonds that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…All said, there may be more “malleability” in the folding trajectory that previously imagined [ 121 ]. The intracellular pathways, aided by chaperones such as PDI and peptidyl prolyl isomerases, may differ from reductionist-derived processes.…”
Section: Learnings From Oxidative Protein Foldingmentioning
confidence: 99%
“…All said, there may be more “malleability” in the folding trajectory that previously imagined [ 121 ]. The intracellular pathways, aided by chaperones such as PDI and peptidyl prolyl isomerases, may differ from reductionist-derived processes.…”
Section: Learnings From Oxidative Protein Foldingmentioning
confidence: 99%
“…Two models for these pathways have been proposed: a "BPTI-like" pathway where all of the folding intermediates contain only the disulfide bonds found in the native structure; and the "hirudin-like" pathway, in which a large number of heterogeneous folding intermediates can form, dominated by intermediates containing non-native disulfide bonds that are rearranged to give the native connectivity (Arolas et al, 2006;Chang, 2011). For many protein architectures, it has been demonstrated that conformational folding drives disulfide bond formation (Welker et al, 2001;Kosuri et al, 2012;Qin et al, 2015;Lv et al, 2018), whereas other proteins adopt intermediate pathways between these two extremes, or can follow different pathways under different conditions (Chang, 2004;Esperante et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 These conditions are widely adopted to mimic physiological conditions favouring the formation of thermodynamically stable folded proteins and cysteine-rich peptides in vitro. [13][14][15] Fig . 1 presents the HPLC chromatograms (C 18 ) of pure linear and folded lt5d.…”
mentioning
confidence: 99%
“… 11,12 These conditions are widely adopted to mimic physiological conditions favouring the formation of thermodynamically stable folded proteins and cysteine-rich peptides in vitro . 13–15 …”
mentioning
confidence: 99%